2012
DOI: 10.1094/pdis-07-12-0615-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Pestalotiopsis clavispora Causing Leaf Spot of Carya illinoensis in Brazil

Abstract: Conspicuous leaf spots in combination with fruit spots were observed for the first time in April and May 2010 on a 30-ha pecan [Carya illinoensis (Wangenh.) K. Koch] orchard in the state of Rio Grande do Sul, Brazil. Initially, tiny grey spots were observed on leaves and, over time, the spots expanded to become gray to light brown circles surrounded by a dark brown border, followed by leaves falling. Eventually, fruits were also attacked, with typical symptoms beginning with tiny water soaked spots which then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Pairwise interactions against human pathogens (Staphylococcus aureus and Candida albicans), a phytopathogen (Rhizopus oryzae), an entomopathogen (Metarhizium anisopliae), and Bacillus subtilis were carried out using previously described methods (Getha and Vikineswary, 2002;Visser et al, 2012). A phytopathogen fungus (Lazarotto et al, 2012;Borrero et al, 2018) identified as Pestalotiopsis clavispora FB1, isolated from Cecropia sp. leaves causing damage to the plant, was also tested.…”
Section: Bioactivity Screeningmentioning
confidence: 99%
“…Pairwise interactions against human pathogens (Staphylococcus aureus and Candida albicans), a phytopathogen (Rhizopus oryzae), an entomopathogen (Metarhizium anisopliae), and Bacillus subtilis were carried out using previously described methods (Getha and Vikineswary, 2002;Visser et al, 2012). A phytopathogen fungus (Lazarotto et al, 2012;Borrero et al, 2018) identified as Pestalotiopsis clavispora FB1, isolated from Cecropia sp. leaves causing damage to the plant, was also tested.…”
Section: Bioactivity Screeningmentioning
confidence: 99%
“…Pestalotiopsis sp. is considered an anamorphic fungus and their spores (conidia) are easily spread, whose penetration occurs in vegetal tissues by natural wounds or openings [9]. In this context, studies involving virulence level of different isolates and other characteristics of pathogenicity are needed [10].…”
Section: Introductionmentioning
confidence: 99%
“…In severe cases, it culminates in fallen leaves and nut production losses, due to a decrease of photosynthetic area (Lazarotto et al, 2012). This pathogen has not yet been reported on pecan; however, it causes significant problems in other species of economic importance as observed for: P. microspora as a causal agent of nut black spot in Carya cathayensis (Chuanqing et al, 2010); P. clavispora causing scab disease in Psidium guajava, in Hawaii (Keith et al, 2006), and as causal agent of leaf blotch in Rosa chinensis, in China (Feng et al, 2014); and Pestalotiopsis spp.…”
Section: Introductionmentioning
confidence: 99%